Southern Lyctus Beetle, Lyctus planicollis LeConte (Insecta: Coleoptera: Bostrichidae: Lyctinae) - Angela S. Brammer (EDIS)
The term "powderpost beetle" is often used to describe two families: Anobiidae (deathwatch beetles) and Bostrichidae (false powderpost beetles). The true powderpost beetles, of the subfamily Lyctinae (formerly family Lyctidae) within the family Bostrichidae, earned their common name from the very fine powdery frass found in their tunnels. Eleven lyctine species have been found in the U.S. Florida has three Lyctus species and one species each in the genera Minthea and Trogoxylon (both subfamily Lyctinae). Of the three Lyctusspecies, one is an introduced seed feeder and another is rarely encountered. Only L. planicollis is common and destructive throughout the South. This document is EENY-283, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2003.